2022
DOI: 10.3389/fonc.2022.829812
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Peripheral Immune Cell Subpopulations After RapidArc/Moderate Hypofractionated Radiotherapy for Localized Prostate Cancer: Findings and Comparison With 3D Conformal/Conventional Fractionation Treatment

Abstract: Radiotherapy (RT) is an important therapeutic option in patients with localized prostate cancer (PC). Unfortunately, radiation treatment causes a decrease in peripheral lymphocytes and, consequently, influences the patients’ immune status. Our aim was to study changes in peripheral blood immune cell subpopulations after RT and during 6 months’ follow-up in 2 groups of PC patients irradiated with different techniques and dose fractions with curative intent. We also investigated the presence of correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Clinical studies have also reported distant responses in patients receiving RT in combination with immune checkpoint inhibitors which were associated with alterations in circulating lymphocyte subsets and antibody responses to tumor-associated antigens [ 35 , 36 , 37 , 38 ]. In addition, there are studies to show changes in circulating immune cell subpopulations and cytokines in cancer patients after RT who did not receive systemic treatment [ 39 , 40 ]. However, so far there is no report to show an effect of RT on the expression of genes involved in immune regulation pathways affecting tumor progression which could further contribute to its immune-activating effects.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also reported distant responses in patients receiving RT in combination with immune checkpoint inhibitors which were associated with alterations in circulating lymphocyte subsets and antibody responses to tumor-associated antigens [ 35 , 36 , 37 , 38 ]. In addition, there are studies to show changes in circulating immune cell subpopulations and cytokines in cancer patients after RT who did not receive systemic treatment [ 39 , 40 ]. However, so far there is no report to show an effect of RT on the expression of genes involved in immune regulation pathways affecting tumor progression which could further contribute to its immune-activating effects.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, our group performed a longitudinal monitoring of the RapidArc/moderate hypofractionation curative radiotherapy effects on the small subpopulations of T lymphocytes DNT, DPT, and NKT in patients treated for localized prostate cancer. DNT, DPT, and NKT cells significantly decreased at the end of RT with slight tendency to recover values during follow‐up, particularly in the hypofractionation group 51 …”
Section: Discussionmentioning
confidence: 94%
“…DNT, DPT, and NKT cells significantly decreased at the end of RT with slight tendency to recover values during follow‐up, particularly in the hypofractionation group. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Because tumor-infiltrating lymphocytes appear to be quite radioresistant, differences in radiosensitivity between circulating lymphocytes and lymphocytes in lymphoid organs may have implications for lymphopenia and thus for considerations of dose prescription and dose scheduling in radiation therapy as well as for fractionation and scheduling of therapies involving both radiation and immune checkpoint inhibitors. An important aspect is also the influence of radiation dose distribution, delivery time and beam arrangement, which has been discussed in the context of highly conformal radiotherapy and its positive effect on lymphopenia ( 114 , 187 ).…”
Section: Discussionmentioning
confidence: 99%
“…The change in the ratio could not be explained by the small difference in radiosensitivities of CD4+ T cells and CD8+ T cells but was presumably caused by radiation-induced priming and mobilization of CD8+ T cells compensating for the loss of CD8+ T cells. Lymphocyte subpopulations in patients after radiation therapy have also been studied in other sites, such as in prostate cancer ( 42 , 114 116 ) and in breast cancer ( 117 , 118 ), demonstrating radiosensitivity of B cells in particular.…”
Section: Radiosensitivity Of Lymphocytesmentioning
confidence: 99%